2020
DOI: 10.4103/jfcm.jfcm_175_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potentially inappropriate medication and its correlates in elderly hospitalized patients: A cross-sectional study based on Beers criteria

Abstract: BACKGROUND: The increase in the prescription of potentially inappropriate medication (PIM) in older adults with significant health consequences is a global concern. This study aimed to determine the prevalence of PIM prescription in older adults as identified by Beers criteria 2015 and 2019. MATERIALS AND METHODS: A cross-sectional study was carried out in older adults aged >65 years at a tertiary care postgraduate teaching hospital. All patients aged ≥65 years irrespec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
5
29
3
3
Order By: Relevance
“…the Beer's criteria 2019. The current study witnessed male predominance (55%) which was found to be similar to other studies 10,11 whereas Zhang H, et al 12 reported predominance of female. The mean age ± SD of the present study population (70.67 ±5.43 years) was found to be less than reported earlier as 75.17 ± 7.66 years 11 and 75.3±7.3 years 12 and higher than reported by Narvekar RS, et al 13 (68.88 years).…”
Section: Total Number Of Pims = 216supporting
confidence: 90%
See 2 more Smart Citations
“…the Beer's criteria 2019. The current study witnessed male predominance (55%) which was found to be similar to other studies 10,11 whereas Zhang H, et al 12 reported predominance of female. The mean age ± SD of the present study population (70.67 ±5.43 years) was found to be less than reported earlier as 75.17 ± 7.66 years 11 and 75.3±7.3 years 12 and higher than reported by Narvekar RS, et al 13 (68.88 years).…”
Section: Total Number Of Pims = 216supporting
confidence: 90%
“…This was found to be consistent with other studies. 10,11 Median length of hospital stay (4.5 days) was found to be less when compared to 6 days in the study conducted by Sharma, et al 10 and 6.44 days by Narvekar R, S et al 13 A higher proportion of the elderly had multiple co-morbidities in the present study and only 15% had a single disease. The average number of diagnoses was found to be 3.61±2.02 This was found to be less than that reported (4.0±2.0) by Zhang H, et al 12 and slightly higher than that reported (3.37) by Narvekar R, S et al 13 69% of the elderly had ≥ 3 diagnoses in the current study which was found to be greater than reported in the study conducted by Sharma, et al 10 (62.5%).…”
Section: Total Number Of Pims = 216contrasting
confidence: 41%
See 1 more Smart Citation
“…The results of our study are similar to the recent study that applied 2019 Beers Criteria on patients aged 65–74 years attending primary care centers in Spain and which reported a PIM prevalence of 68.8% [ 22 ]. Furthermore, another recent study by Sharma et al reported that nearly 62% of older patients aged 65–70 years received at least one PIM during hospitalization [ 23 ]. To date, there are no data available on T2DM patients using the latest version of Beers Criteria 2019 with which to make any comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that hypertension (49.3%) was the most common comorbidity in older patients with T2DM. The results are compared with various research studies that showed hypertension to be the primary cause of morbidity in the older population with T2DM [ 23 ].…”
Section: Discussionmentioning
confidence: 99%